Choosing A Competence, Education And Work Discipline On The Productivity Of Food Security And Agricultural Services For The Future - Heni Rochaeni; Ellin Herlina; Mahfud (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — find out whether competence, Education, and work discipline affect work productivity either partially or simultaneously.Research method— Causal associative research with a quantitative approach using a questionnaire survey method. The population in the study was the staff of the Food and Agriculture Security Service "KNG", which amounted to 206 people and then reduced using the slovin formula so that it became 68 samples.Result— the results of the t-test are obtained that the tcount value of the Competence variable (X1) has a p-value of 0.000 <0.05, meaning that it is significantly distributed, while count 5.775 > from table 1.997 means significant. (table 1.997 obtained from degrees of freedom (df) n-3 or 68-3=65. The results of the t-test show that the t-count value of the Education variable (X2) has a p-value of 0.000 <0.05, which means it is significant, while tcount is 6.287 > from table 1.997, which means it is significant. And for the tcount value of the Work Discipline variable (X3), it has a p-value of 0.000 <0.05 which means it is significant, while tcount is 2.804 > from table 1.997, which means it is significant.Conclusion— First: There is a positive and significant influence partially Competence on Employee Productivity of the Food and Agriculture Security Service of “KNG” . The magnitude of the influence of Competence on Employee Productivity is 94%. Second: There is a positive and partially significant effect of Education on the Productivity of the Food and Agriculture Security Service of Kuningan Regency employees of 87.7%. Third: There is a positive and significant influence partially Work Discipline on the Productivity of the Employees of the Food Security and Agriculture Office of “KNG” 82.2%. Fourth: There is a simultaneous positive and significant effect of Competence, Education and Work Discipline on Employee Productivity at the Food and Agriculture Security Service of “KNG”. The magnitude of the positive influence of Competence, Education, Work Discipline on Employee Productivity is 96.4% while the remaining 3.6% is influenced by other factors. With increasing competence, Education and work discipline, mployee productivity will also increase.